2017
DOI: 10.1111/poms.12647
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Platform's In‐App Advertising Contract Under Agency Pricing for App Sales

Abstract: Unlike advertising in traditional media, a mobile platform's in‐app advertising market exhibits two unique features—split structure of the mobile platform with a platform owner and an app developer jointly provisioning in‐app advertising, and agency pricing for app sales. We develop a two‐sided market model to analyze the role of these two unique features in determining the platform owner's optimal advertising revenue‐sharing contract. Our results reveal an interesting N‐shaped dynamic regarding the platform o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 27 publications
0
64
0
Order By: Relevance
“…Then the number of premium content acquired through viewing ads is rn and the corresponding nuisance cost is cn (Anderson and Coate , Anderson and Gabszewicz , Hao et al. ), where c=cLorcH. Suppose the consumer also buys q units of premium content.…”
Section: Modeling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the number of premium content acquired through viewing ads is rn and the corresponding nuisance cost is cn (Anderson and Coate , Anderson and Gabszewicz , Hao et al. ), where c=cLorcH. Suppose the consumer also buys q units of premium content.…”
Section: Modeling Frameworkmentioning
confidence: 99%
“…Concerning the latter issue, Gabszewicz et al (2005) showed that a monopolistic media firm would lower its newspapers' price when it starts to profit from advertising spaces. Hao et al (2017) showed that a mobile app developer would reduce the app price to enlarge its app user base if she chooses to become an in-app ad publisher. Sun and Zhu (2013) empirically found that content providers would tailor their content as well as improve their content quality once they start to earn ad profit from the traffic to their content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the 'sojourn' and 'exposure' effects, Sun et al study the ad-sequencing problem of fading ads shown to App users, without considering the role of the platform [45]. Hao et al discuss paid Apps and the revenue-sharing policy of the platform under in-App advertising mode [1]. Chen et al extend the model to discuss the strategic choice between paid Apps and free Apps with in-advertising mode when App developers face multiple platforms [46].…”
Section: Online Advertisingmentioning
confidence: 99%
“…In contrast, the revenue source of an App is more from in-App advertising than from sales. In-App advertising is a mode in which an App developer embeds advertisers' ads into App, and when the users click or watch the ads, the advertiser will pay App developer by a certain billing way [1]. However, even if in-App advertising brings huge advertising revenue to the developers, it also carries an immeasurable risk of damaging the user experience and causing annoyance to users, which is the great dilemma brought by this mode to the App developers [2].…”
Section: Introductionmentioning
confidence: 99%
“…, Hao et al. ). We make contributions to the literature gap of advertising platforms’ revenue maximization using offline operations by empirically studying a large classified ads website.…”
Section: Introductionmentioning
confidence: 99%